Inductive Training Model in Improving Teacher Competence through Teacher Working Groups - Linda Zakiah; Zulela. MS; Edwita Edwita (Pendidikan Administrasi Perkantoran, Universitas Negeri Makassar, 2021)
Professionalism is a demand in various professions, including elementary school teachers. The important thing in a profession is a professional attitude and quality of work. This research was conducted with the aim of providing an overview of how the inductive training model develops attitude assessment instruments in improving teacher competence through teacher working groups in accordance with the steps of the inductive training model. The research approach used in this study is a descriptive qualitative approach to obtain information on how the inductive training model improves teacher competence through teacher working groups. In general, there are four data collection techniques used in this study, namely participant observation, in-depth interviews, documentation studies, and combination/triangulation. The steps in implementing the inductive training model are starting with measuring the ability of the trainees; grouping of abilities in the area of the training program; compare participants' abilities with training materials; establish ability and skills gaps; developing training processes; then carry out the training; and carry out research and measurement. The research was conducted by conducting pretest and posttest with the results obtained after carrying out training on developing an attitude assessment instrument, post-test results increased by 97%.